Cubic Superparamagnetic Nanoparticles of Nife2o4 Via Fast Microwave Heating - Casagrande-Denardin, J (Kluwer Academic Publishers, 2014)
This study demonstrated the possibility of using microwave heating as a fast and cheap method for synthesizing superparamagnetic nanoparticles. In this sense, NiFe2O4 samples were subjected to microwave heating at various temperatures to determine the lowest temperature at which the crystalline phase of the nanoparticles occurs. X-Ray powder diffraction, 57Fe Mössbauer spectroscopy, and transmission electron microscopy of the samples were performed to confirm the formed nanoparticles. It was observed a cubic structure of inverse spinel type with good crystallinity. The magnetic properties of the samples were studied using a vibrating sample magnetometer and was found to zero values to remanent magnetization and coercivity field. This behavior suggests superparamagnetic features for all samples. The crystallite size (9, 10, and 12 nm) and saturation magnetization (31–45 emu/g) were used as a function of the increase of the temperature treatment time. Blocking temperature was found by tracing remanent magnetization versus temperature. © 2014, Springer Science+Business Media Dordrecht.